Revisión sistemática de literatura: estado actual de la inteligencia artificial en las instituciones de educación superior del Ecuador. - Cabrera Sarango, Miguel Antonio (2020)
During the last years in the Higher Education Institutions (IES) of Ecuador the use of Artificial Intelligence (AI) has increased; in the past the technology was thought fictitious or very remote to the existence and availability of various applications in different fields. The objective of this Thesis (T) is to develop a Systematic Literature Review about current state of Artificial Intelligence in Higher Education Institutions of Ecuador; to this aim, the research question is: What is the current situation of Artificial Intelligence in Higher Education Institutions in Ecuador? This T was executed in two phases, the first phase through a search for Systematic Literature Reviews (SLR) in the field of engineering, to serve as a basis for the designed and development of a proposal of SLR methodology for using in the field of Computer Science specifically in AI. As a second phase, it developed the SLR process designed in the previous phase; three stages were defined and guidelines were established for each of them. This SLR process is characterized by: 1) Planning, 2) Execution, 3) Report. Searches were performed on Google Scholar, ACM, IEEE, Science Direct and Scopus from 2010 to July 2019. About 4,598 studies were identified, of which 191 valid studies were selected. In the SLR obtained as a result, that the areas with the highest scientific production related to AI are: “Machine learning” (20.94%), “Artificial Neural Network” (16.75%), “Data Mining” (11.51%), and Big Data (9.94%). While the areas with the lowest scientific production are "Robotics" (4.18%), "Human Computer Iteration" (3.14%), "Natural Language Processing" (2.61%), "Genetic Algorithms" (2.09%) and "Experts System" (1.57%). In addition, VOSviewer software was used to visualize two bibliometric networks (co-authorship and co-relationship), it allowed to identify the co-authorship and the impact of AI areas among researchers from Ecuador and the world. Also, it observed to 48 research groups in the field of AI, 113 IES in 32 countries linked to Ecuadorian researchers. In conclusion, in Ecuador the empirical evidence was found to identify the current situation of AI; indicating there are 32 IES in Ecuador that carry out publications related to the AI field, and these researchers have increased their scientific production year by year, especially since 2017.